I-MABRUR APPLICATION BASED ON WEBSITE (CASE STUDY: PT PAKUAN JAYA SAFARI TRAVEL) - Arief Syafrudin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
PT. Pakuan Jaya Safari Travel in its business activities there are a number of constraints faced which are still limited, namely the absence of a website-based application concerns the information of the Hajj and Umrah program to prospective pilgrims. Today the company uses stand-alone software, has not been integrated with other functions such as using the Microsoft Excel application, seeing how it works that slows down the process of managing data and information and in decision making by management. Therefore, Website-Based I-Mabrur Application with analytical methods of Performance, Information, Economics, Control, Efficiency, Service (PIECES) can overcome existing problems and improve service quality for pilgrims in the process of Hajj and Umrah activities.